Interview with Owen McCafferty Scenes from the Big Picture - Verçosa, Fernanda (ABEI Journal, 2013)
The following interview took place at Queen’s University Belfast, Northern Ireland, in August 2011. Owen McCafferty talks about his work and,in particular, on Scenes from the Big Picture. The technique of writing a playand of consructing scenes and characters is raised together with his views on translation.Keywords: Owen McCafferty; Scenes from the Big Picture; writing a play;translation.